Enhancing Mar and Abrasion Resistance of Acrylic Hard Coatings with Soft Base Layer - Chouwatat, Patcharida; Kotaki, Masaya; Yokohama, Atsushi (Scientific Research, 2016)
Mar and abrasion resistance were investigated by a progressive load scratch test and steel wool abrasion test, respectively. Two acrylic coating systems including trimethylolpropane triacrylate (TMPTA) and pentaerythritol triacrylate (PETA) were prepared. A soft base layer was introduced as an intermediate layer between two different types of top layer and poly (methyl methacrylate) (PMMA) substrate to demonstrate the effect of soft base layer on mar and abrasion resistance. Abrasion damage on the coating surface was found to be less severe, when the soft base layer was incorporated into the coating systems. The reduction in scratch coefficient of friction (SCOF) and surface roughness was also observed. The results suggested that mar and abrasion resistance was greatly influenced by the presence of soft base layer, although different top layers were used. Moreover, it was found that abrasion resistance was further improved as the thicker soft base layer was applied.
Keywords: Acrylic Coating; Soft Base Layer; Mar Resistance; Abrasion Resistance